Why should change the universities assessment practices? towards the recognition of the subject of assessment’s voice (Praxis Educativa, 2012)
In the changing reality that has impacted the contemporary university, we reflected upon the necessary changes that must occur in professional training, particularly, in the assesmnent practice. Among the challenges stated, the need to identify the new type of student entering higher education and the new paradigms underlying educational changes are considered. The challenges are directed to reconceptualize processes regarding the student as a subjec of meaning and above all, to explore new methods to plan a motivating and productive assesment. This must consider students’ knowledge, skills and abilities as crucial elements in the learning process.
Keywords: university; assessment; change; learning; challenges